Dose calculation errors as a component of failing IROC lung and spine phantom irradiations. Issue 9 (23rd June 2020) - Edward, Sharbacha S.; C. Glenn, Mallory; Peterson, Christine B.; Balter, Peter A.; Pollard‐Larkin, Julianne M.; Howell, Rebecca M.; S. Followill, David; Kry, Stephen F.
Abstract : Purpose: Between July 2013 and August 2019, 22% of the imaging and radiation oncology core (IROC) spine, and 15% of the moving lung phantom irradiations have failed to meet established acceptability criteria. The spine phantom simulates a highly modulated stereotactic body radiation therapy (SBRT) case, whereas the lung phantom represents a low‐to‐none modulation moving target case. In this study, we assessed the contribution of dose calculation errors to these phantom results and evaluated their effects on failure rates. Methods: We evaluated dose calculation errors by comparing the calculation accuracy of various institutions' treatment planning systems (TPSs) vs IROC‐Houston's previously established independent dose recalculation system (DRS). Each calculation was compared with the measured dose actually delivered to the phantom; cases in which the recalculation was more accurate were interpreted as a deficiency in the institution's TPS. A total of 258 phantom irradiation plans (172 lung and 86 spine) were recomputed. Results: Overall, the DRS performed better than the TPSs in 47% of the spine phantom cases. However, the DRS was more accurate in 93% of failing spine phantom cases (with an average improvement of 2.35%), indicating a deficiency in the institution's treatment planning system. Deficiencies in dose calculation accounted for 60% of the overall discrepancy between measured and planned doses among spine phantoms. In contrast, lung phantom DRS calculations were more accurate in only 35% and 42% of all and failing lung phantom cases respectively, indicating that dose calculation errors were not substantially present. These errors accounted for only 30% of the overall discrepancy between measured and planned doses. Conclusions: Dose calculation errors are common and substantial in IROC spine phantom irradiations, highlighting a major failure mode in this phantom and in clinical treatment management of these cases. In contrast, dose calculation accuracy had only a minimal contribution to failing lung phantom results, indicating that other failure modes drive problems with this phantom and similar clinical treatments.